Utilización de la metodología six sigma para el mejoramiento del proceso de servicios del taller de un concesionarío de vehículos, Guayaquil - Silva, Kleber (2009)
The following research has been developed in the Maintenance and Repair department of a car dealer which sold from the start heavy and small cars, for that reason, a brief explanation of the process is made. The lack of control in the first stages of repair causes the corrective of the last stages go to defectes that slow down the delivering process, which is the greatest cause of unconformity of the customer. During the development of the research, specificly during the definition stage, the problem to be solved is described, the causes and the variables invloved using tools as VOC and business process mapped. Finally the corrective actions on the worst issues of the process of car Maintenance and Repair previously identified through and analysis, using statistical tools.